1995
DOI: 10.1136/jcp.48.6.519
|View full text |Cite
|
Sign up to set email alerts
|

Circulating endothelin-1 concentrations in patients with chronic hypoxia.

Abstract: Aims-To evaluate the behaviour ofplasma endothelin-1 in patients with chronic hypoxia. Methods-Fifteen male patients (mean age 52-1 + 3-1 years) with mild chronic obstructive pulmonary disease (COPD) were studied. Twelve healthy men (mean age 48 3 +5 54 years) served as controls. Both patients and controls underwent standard pulmonary function tests, echocardiographic evaluation, and arterial blood gas evaluation. Blood samples for endothelin-l assay were taken from a previously incannulated antecubital vein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
34
1
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 26 publications
7
34
1
1
Order By: Relevance
“…However, all relevant studies are consistent in showing that the ET-1 levels are significantly increased in cases of pulmonary hypertension. The most dramatic increases in circulating ET-1 levels and ET-1 expression, appear to be associated with primary pulmonary hypertension (Stewart et al, 1991;Cacoub et al, 1993;Giaid et al, 1993;Nootens et al, 1995); although ET-1 levels are also significantly increased in pulmonary hypertension secondary to hypoxia (Stewart et al, 1991;Ferri et al, 1995), congenital heart defects (Yoshibayashi et al, 1991;Cacoub et al, 1993;Vincent et al, 1993), valvular heart disease (Stewart et al, 1991;Chang et al, 1993;Yamamoto et al, 1994;Zhu et al, 1994), chronic heart failure (Cody et al, 1992;Kiowski et al, 1995) and the adult respiratory distress syndrome (Langleben et al, 1993). Plasma ET-1 levels can be increased four fold in some of these studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, all relevant studies are consistent in showing that the ET-1 levels are significantly increased in cases of pulmonary hypertension. The most dramatic increases in circulating ET-1 levels and ET-1 expression, appear to be associated with primary pulmonary hypertension (Stewart et al, 1991;Cacoub et al, 1993;Giaid et al, 1993;Nootens et al, 1995); although ET-1 levels are also significantly increased in pulmonary hypertension secondary to hypoxia (Stewart et al, 1991;Ferri et al, 1995), congenital heart defects (Yoshibayashi et al, 1991;Cacoub et al, 1993;Vincent et al, 1993), valvular heart disease (Stewart et al, 1991;Chang et al, 1993;Yamamoto et al, 1994;Zhu et al, 1994), chronic heart failure (Cody et al, 1992;Kiowski et al, 1995) and the adult respiratory distress syndrome (Langleben et al, 1993). Plasma ET-1 levels can be increased four fold in some of these studies.…”
Section: Resultsmentioning
confidence: 99%
“…ET-1 was identified in 1989 in human plasma by radioimmunoassay [5], and its level was found to be increased in several diseases, such as atherosclerosis [4], myocardial infarction [6], renal disease [7], and systemic [8]and pulmonary hypertension [9]. Recent studies have shown that the plasma ET-1 level is increased in patients with COPD compared with normal subjects [10, 11]. However, the pathophysiological roles of the increase in plasma ET-1 level in patients with COPD remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, chronic hypoxia is a condition with elevated ET-1 plasma levels 6 and in a rat model of chronic hypoxia enhanced ET-1 and endothelin receptor expression was found. 7 Conflicting data, however, exist on the effect of acute hypoxia on the release of ET-1.…”
mentioning
confidence: 99%